Polarization of Nucleons in the Deuteron Stripping Reaction on Nuclei - Kovalchuk, V. I. (Russian physics journal, 2018)
A general analytical expression has been obtained in the diffraction approximation for the polarization of nucleons arising in the deuteron stripping reaction on nuclei at intermediate energies of the incident particles. A tabulated density distribution of the target nucleus and a realistic wave function of the deuteron with correct asymptotic limits at large internucleon distances were used in the calculations. The nucleon-nucleus phase shifts were calculated in the Glauber formalism using the double folding potential. The calculated angular dependences for the vector analyzing power Ay of the reaction 3 He( d , p) 4 He are found to be in satisfactory agreement with the corresponding experimental data.